How sweet it is - Gunn, Sophie (New York : Forever, 2011)
"Single mom Lizzie Bea Carpenter knows no white knight will save her. A hardworking waitress at the local diner, she's raising her daughter to be like the independent women in her 'Enemy Club'--high school rivals turned best friends, who always tell each other the whole truth and nothing but! Yet part of Lizzie wishes she did have a man's help, just for things like fixing up the house. Enter Dante 'Tay' Giovanni: sexy, kind, and offering assistance--no strings attached. Slowly, steadily, Lizzie's heart opens. But the grip of the past is fierce, and nothing in life is ever really free. Tay has his own tragedies to overcome, but if he can, he'll fix more than Lizzie's home. He'll show her just how sweet it is to [be] loved by him."--P. [4] of cover.
Keywords: Single mothers -- Fiction; Waitresses -- Fiction; Man-woman relationships -- Fiction; Love stories